Strategic manufacturing priorities for South African manufacturers: The need to shift emphasis and improve on current performance levels - L. P. Kruger (South African Journal of Business Management, 1997)
The findings of an empirical research project show that the majority of so-called large South African manufacturers acknowledge that manufacturing-based strategies enhance the competitive capabilities and advantages of their firms and that this contributes to long-term, superior business performance and success. They also recognize that superior manufacturing capabilities will be prerequisites for the improvement on both their national and international competitive positions in the future. To better their positions in these markets, the manufacturers need to shift their emphasis (in order of priority) to: (1) high quality, low cost and high dependability, all of priority number (1); (2) high speed; and (3) high flexibility. they also need to improve on their current performance levels in all of these strategic manufacturing priorities by an average of between 20% and 30%.
Keywords: 650